2011
DOI: 10.1001/archdermatol.2011.178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pruritus on Quality of Life

Abstract: To compare the impact of chronic pruritus and chronic pain on quality of life (QoL) using directly elicited health utility scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
215
0
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(226 citation statements)
references
References 18 publications
2
215
0
9
Order By: Relevance
“…Itch (pruritus) is an unpleasant sensation that elicits the desire (or reflex) to scratch. Itch has many similarities to pain; indeed, it was referred to as the "skin equivalent of chronic pain" (Kini et al, 2011). Chronic itch is a large, unmet medical need.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…Itch (pruritus) is an unpleasant sensation that elicits the desire (or reflex) to scratch. Itch has many similarities to pain; indeed, it was referred to as the "skin equivalent of chronic pain" (Kini et al, 2011). Chronic itch is a large, unmet medical need.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…Pruritus affects different physical, social and psychological aspects of the life. It can cause sleep disturbances, agitation, and anxiety and can reduce concentration, sexual desire and sexual function (1,3,(7)(8)(9). Therefore, treatment of pruritus is an important point in the management of many skin and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies found that itch causes just as much quality-of-life disturbance as does pain. 5 Chronic pruritus negatively effects all patients' activities of daily living and their emotional well-being. 3,4 Despite itch being a commonly reported symptom, 6 it is not routinely assessed by most clinicians.…”
Section: Lack Of Appreciation Of the Patient-burden Of Pruritusmentioning
confidence: 99%